Estratégia de modelagem por algoritmo genético adaptativo para programação reativa da produção de produtos com uso simultâneo de máquinas e sistemas de transporte em sistemas de manufatura - Sanches, Danilo Sipoli (2008)
The production scheduling problem of products with simultaneous use of machines and transportation systems in manufacturing systems invloves the system modeling task and the application of a technique to solve it. This scheduling type is characterized by the great amount of possible solutions and several researches indicates the Adaptive Genetic Algorithms as search method to solve this problem, where these algorithms have the capacity of globally explore the search space and to find good solutions quickly. In this dissertation, it is proposed a method that uses an adaptive genetic algorithm to solve this scheduling problem. The aim of this dissertation is to obtain good scheduling of product production, in order to reach good makespan values and response obtaining time. The makespan values are obtained by adaptive genetic algorithm and the response obtaining time is the processing time of the adaptive genetic algorithm. The results were validated in small and large scenerios and compared with the results of two other approaches. These results are presented and discussed in this dissertation.